Boundary element and transfer operator methods for multi-component wave systems - Ben Hamdin, Hanya Abdusalam Mohamed (2012)
In this thesis, exact and semiclassical approaches are derived for predicting wave energy distributions in coupled cavities with variable material properties. These approaches are attractive because they can be extended to more complex built-up systems.